Ultrasound and magnetic resonance imaging findings in Schistosomiasis mansoni: expanded gallbladder fossa and fatty hilum signs - Luciana Cristina dos Santos Silva; Luciene Mota Andrade; Ivie Braga de Paula; Leonardo Campos de Queiroz; Carlos Maurício Figueiredo Antunes; José Roberto Lambertucci (Revista da Sociedade Brasileira de Medicina Tropical, 2012)
INTRODUCTION: There is no study relating magnetic resonance imaging (MRI) to ultrasound (US) findings in patients with Schistosomiasis mansoni. Our aim was to describe MRI findings inpatients with schistosomal liver disease identified by US. METHODS: Fifty-four patients (mean age 41.6±13.5years) from an area endemic for Schistosomiasis mansoni were selected for this study.All had US indicating liver schistosomal fibrosis and were evaluated with MRI performed witha 1.5-T superconducting magnet unit (Sigma). RESULTS: Forty-seven (87%) of the 54 patientsshowing signs of periportal fibrosis identified through US investigation had confirmed diagnosesby MRI. In the seven discordant cases (13%), MRI revealed fat tissue filling in the hilar periportalspace where US indicated isolated thickening around the main portal vein at its point of entryto the liver. We named this the fatty hilum sign. One of the 47 patients with MRI evidence ofperiportal fibrosis had had his gallbladder removed previously. Thirty-five (76.1%) of the other46 patients had an expanded gallbladder fossa filled with fat tissue, whereas MRI of the remainingeleven showed pericholecystic signs of fibrosis. CONCLUSIONS: Echogenic thickening of thegallbladder wall and of the main portal vein wall heretofore attributed to fibrosis were frequentlyidentified as fat tissue in MRI. However, the gallbladder wall thickening shown in US (expandedgallbladder fossa in MRI) is probably secondary to combined hepatic morphologic changes inschistosomiasis, representing severe liver involvement.